Penegakan Hukum Terhadap Tindak Pidana Kepabean Penyeludupan Pakaian Bekas (Putusan No. 237/Pid.B/2016/PN.Tjb) - Roberto Tambunan; Suhatrizal Suhatrizal; Taufik Siregar (JUNCTO: Jurnal Ilmiah Hukum, 2019)
Smuggling is a problem that often occurs in Indonesia, so the smuggling problem must receive the full attention of the government to be immediately addressed. As a national legal product based on the Pancasila and the 1945 Constitution, the form of the Proactive and Anticipatory Customs Law is still very simple, on the other hand it must reach a broader aspect to anticipate the development of trade. The method of this research is Library Research and Field Research. The negative impact of smuggling used clothing is very detrimental to the domestic industry and detrimental to the country's income and economy, but on the other hand there are also positive impacts on the poor that benefit from being able to buy ex-foreign goods from smuggling at low prices and higher quality high. As one of the Government Agencies participating in the effort to eradicate the smuggling of used clothing and the public should not be easily tempted by the import price of used clothing which is cheaper than local clothing, because the level of health is not necessarily guaranteed.